2017
DOI: 10.4018/ijicte.2017040107
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Students' Adoption of ICT Tools in Higher Education Institutions

Abstract: In the recent years, technology has been an important component in teaching and learning. The literature has highlighted many studies investigations on the students' intention to use technology in many Western, African and South East Asian countries. This article brings in the factors influencing students' adoption of ICT tools in higher education institutions in India. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was used to determine the predictors of ICT adoption in learning their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…223 and (63%) Inadequate of technical support as well as (71%) lack of time. However the results of this section agreed with others studies conducted in different countries around the world such as the one by [7] [19]. From the results it shows that, there is relation between many barriers, Teachers cannot use ICT tools appropriately in classroom, because they need support and equipment's.…”
Section: Barriers Of Information Communiction Technology (Ict) Adoptisupporting
confidence: 88%
See 1 more Smart Citation
“…223 and (63%) Inadequate of technical support as well as (71%) lack of time. However the results of this section agreed with others studies conducted in different countries around the world such as the one by [7] [19]. From the results it shows that, there is relation between many barriers, Teachers cannot use ICT tools appropriately in classroom, because they need support and equipment's.…”
Section: Barriers Of Information Communiction Technology (Ict) Adoptisupporting
confidence: 88%
“…Thus ICTs in the teaching and learning environment will contribute in molding learners from a younder age until maturity when they are able to join the work force. Studies done have shown that adoption of ICT in the teaching and learning process benefits students through improving the problem solving skills, improve comprehension skills, improve their reasoning, make them innovative, and make them to be part of the global society by improving their competitive urge to succeed thus overall improvement in reasoning [3,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for the Universities to incorporate ICT in four major areas under administrative management, namely financial management, management of infrastructure and office management including management of records and communications. Adoption of ICT in higher education in India needs further exploration (Rosaline and Wesley, 2017). Nevertheless, there are examples of adoption of ICT by Indian universities from the private and public sector.…”
Section: Use Of Ict In Educational Administrationmentioning
confidence: 99%
“…The Unified Theory of Acceptance and Use of Technology (UTAUT) demonstrate was utilized to discover the elements of ICT appropriation in learning their coursework in schools. The information were gathered from 398 students doing their undergrad building programs and in the wake of applying basic condition demonstrating, the discoveries demonstrated that execution hope, exertion anticipation and social impact has a positive critical effect on conduct goal to utilize ICT instruments and encouraging conditions has an immediate contact with use conduct [13]. Samiaji Sarosa(2017), paper on "I need to purchase iPad Mini: The UTAUT Perspective" studied on the acknowledgment on of iPad Mini for supporting scholarly exercises.…”
Section: Literature Reviewmentioning
confidence: 99%